A paisagem como recurso e o geoturismo como possibilidade em Mucajaí - RR - Veras, Ana Sibelônia Saldanha (2014)
The county of Mucajaí ( focus area of this study ) is located in the central- west region of the state of Roraima . The analysis of the landscape of the county of Mucajaí (subject of this study ) focuses on the geological and geomorphological aspects and its potential for geotourism. To develop the research, it was necessary lifting bibliographic, cartographic and remote sensing equipment, as well as field activities aiming to identify and describe the geomorphological compartments that were subsequently mapped. As a result, we obtained a description of the landscape in its geological and geomorphological context in which we identified the modeled denudation and accumulation. The partitioning study revealed the following units : Relief on Structured Crest, this unit represents a relief of differential erosion, covered by vegetation of Dense Ombrophilous Forest; stood out features such as mountains, waterfalls ; in the Somital Convex Surface, is distributed in a defined and isolated manner throughout massive flat surface that occurs singly , called residual relief beyond relief Structured Convex. The recessed areas are represented by Planed Surfaces and Alluvial . The landscape of the studied area reveals a great potential for geotourism activity, like mountains and hills lined and beautiful waterfalls. Therefore, the potential landscape full of natural scenic beauty favoring a large potential for the deployment of geotourism activity, from existing initiatives in the county and planning aimed at exploiting the potential for its effective operationalization.